Implementasi RESTful untuk Mengurangi Mean Time to Resolve pada Alert Handling - Yadhi Aditya; Setiadi Rachmat; Maisevli Harika; Mufqi Uwais Nastiar Salim; Dewanto Joyo Pramono (JURIKOM (Jurnal Riset Komputer), 2022)
One of the responsibilities of the company's IT infrastructure team is ensuring that IT services or services stay available. One part of analyzing the performance of IT infrastructure is MTTR (Mean Time to Resolve) or the average time necessary to restore a service that is experiencing issues. Warnings or alerts are shown when a service is encountering difficulties. As a member of the IT infrastructure team, the on-call engineer is responsible for managing alarms. At PT Sense Health Indonesia, difficulties manifest in the form of recurrence alerts, or warnings resulting from previously fixed or rectified issues. This warning is repeated with sufficient frequency to enhance the MTTR value. The findings demonstrated that the integration of tools using the RESTful approach streamlined the process of processing alerts. The deployment led to a 78% decrease in the average time required to handle alarms. This study contributes by demonstrating one method for decreasing MTTR for alert handling